Exploration of the induced cytokine responses in European Lyme neuroborreliosis: A longitudinal cohort study - Rosa Maja Møhring Gynthersen; Mathilde Ørbæk; Helene Mens; Christian Stenør; Lothar Wiese; Sisse Rye Ostrowski; Susanne Dam Nielsen; Anne-Mette Lebech (Ticks and Tick-Borne Diseases, 2023)
Lyme neuroborreliosis (LNB) is a prevalent tick-borne disease in Europe caused by Borrelia burgdorferi sensu lato complex. Slightly suppressed induced Th1- and Th17-responses are seen at diagnosis. The induced immune response following antibiotic therapy is unknown. We hypothesized that the immune responses normalize after completing antibiotic treatment.An observational longitudinal cohort study investigating the induced immune response in adult patients with LNB at diagnosis, three and six months after treatment. Whole blood was added to three TruCulture® (Myriad RBM, Austin, USA) tubes each containing one stimulation. An additional TruCulture® tube was without stimulation representing the in vivo activation of blood immune cells. Nine cytokines were measured using Luminex (LX200, R&D Systems, BIO-Teche LTD). Changes in immune response were analyzed with linear mixed model including follow-up as categorical fixed effect.A total of 21 patients with 55 samples were included. All had clinical improvement, but 5/21 patients reported residual symptoms after six months. The non-induced release of IL-17A and IL-1β increased significantly from diagnosis to six month follow-up. Six months after treatment only IFN-α and TNF-α were below the reference range.Minor variations in the induced immune responses were seen during the study period. Th1- and Th17-responses continued to be low with low IFN-γ, IL-12p40, and IL-17A in multiple stimulations.Overall little dynamic was observed. The changes in the cytokine responses are most likely not linked to LNB pathogenesis and our results do not support the implementation of TruCulture® in the diagnostics or follow-up of LNB.